A Simple Method for Estimating Age-Specific Rates from Sequential Cross Sections. - Schmertmann, Carl P. (Demography, 2002)
I develop and demonstrate a simple formula for estimating age-specific event rates for a period from “before” and “after” cross sections. The general approach applies to a wide range of estimation problems in demography, the social sciences, and epidemiology. The method arises from the formal mathematics of unstable populations and is similar in spirit to “variable-r” methods. Unlike those methods, however, the new technique does not require specialized computer programming or iterative calculations, and event rates can be calculated directly from cross-sectional data in simple spreadsheets. The article includes a formal mathematical exposition of the method, simulation tests, and several examples. Reprinted by permission of the publisher.